Ethical Leadership as a Catalyst for Ethical Synergy between Ethics and Performance of Civil Servant : A Study of the Gunungkidul Regency Government - Sunaryanta Sunaryanta; Leyaket Ali Mohamed Omar (Universitas Muhammadiyah Ponorogo, 2026)
This research aims to analyse how ethical leadership as a catalyst for synergy between ethics and performance of the state apparatus in Gunungkidul district government and the factors that cause it. This research uses a descriptive qualitative approach with ethnographic method. The etnographic method aims to deeply understand the culture, values, practices and perspectives of factors in a specific government context. Data collection involved secondary data obtained through review and analysis of previous studies and primary data obtained through observation. The theory used in this research is ethical leadership theory, which includes integrity, honesty and moral responsibility toward others. Ethical theory consists of values. Principles, standards and norms of behaviour and government performance theory measured by input, output,outcome and impact indicators. The result indicate that the Gunungkidul district government has great potential to make ethical leadership a driver of ethics and performance synergy. Although its implementation has not been uniform at all levels. This unevenness is influenced by several factors such as different interpretations of the code of ethics, inconsistent supervision, different leadership examples and resistance from different organisational cultures.